2016
DOI: 10.15171/jcs.2016.010
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Professionalism of Nurses Working in a Hospital in Turkey

Abstract: Introduction: Professionalism is characterized by the degree of dedication displayed by individuals regarding the values and behavioral attributes of a specific career identity. Professionalism indicates attitudes that represent high levels of identification with and commitment to a specific profession. In the process of the professional development of nursing, various factors affect these obstacles which may impede the professional development of nurses and their professional behaviors. This study was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 19 publications
2
53
0
4
Order By: Relevance
“…Miller, Adams, and Beck () identified basic attributes of a profession as including educational preparation, research, competence, continuing education, and autonomy, which distinguishes professionals from other workers. In recent years, nursing has focused on expansion of the profession in rapidly changing healthcare environments (Dikmen, Karataş, Arslan & Ak ), mainly due to social, cultural, scientific, and technological changes. The global economic crisis in 2008 and beyond has had huge impacts on health sector funding and employment, with austerity measures affecting service provision and all professionals groups including nurses (Buchan, O'May & Dussault ).…”
Section: Introductionmentioning
confidence: 99%
“…Miller, Adams, and Beck () identified basic attributes of a profession as including educational preparation, research, competence, continuing education, and autonomy, which distinguishes professionals from other workers. In recent years, nursing has focused on expansion of the profession in rapidly changing healthcare environments (Dikmen, Karataş, Arslan & Ak ), mainly due to social, cultural, scientific, and technological changes. The global economic crisis in 2008 and beyond has had huge impacts on health sector funding and employment, with austerity measures affecting service provision and all professionals groups including nurses (Buchan, O'May & Dussault ).…”
Section: Introductionmentioning
confidence: 99%
“…The level of professionalism demonstrated by nurses, and the resulting image created, is increasingly crucial in attracting clients. The present study aimed to investigation and analysis of Nurses Working Professionalism Using a demographic questionnaire and Behavioral Inventory Form for Professionalism in Nursing (BIPN) [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was found that the majority of participants did not attend scientific congresses, did not listen to a research presentation about nursing, did not read nursing research and did not conduct research after graduation. Both this study and different studies in the literature have shown that the participation rate of nurses in scientific activities is very low (15)(16)(17). Scientific activities are one of the ways to provide nurses to use the results of scientific research, which constantly renews and adds dynamism to the content and quality of nursing care.…”
Section: Discussionmentioning
confidence: 77%